Lipophilicity Assessment of Ruthenium(II)-Arene Complexes by the Means of Reversed-Phase Thin-Layer Chromatography and DFT Calculations - Khalil Salem A. M. Shweshein; Filip Andrić; Aleksandra Radoičić; Matija Zlatar; Maja Gruden-Pavlović; Živoslav Tešić; Dušanka Milojković-Opsenica (The Scientific World Journal)
The lipophilicity of ten ruthenium(II)-arene complexes was assessed by reversed-phase thin-layer chromatography (RP-TLC) on octadecyl silica stationary phase. The binary solvent systems composed of water and acetonitrile were used as mobile phase in order to determine chromatographic descriptors for lipophilicity estimation. Octanol-water partition coefficient, logKOW, of tested complexes was experimentally determined using twenty-eight standard solutes which were analyzed under the same chromatographic conditions as target substances. In addition, ab initio density functional theory (DFT) computational approach was employed to calculate logKOW values from the differences in Gibbs’ free solvation energies of the solute transfer from n-octanol to water. A good overall agreement between DFT calculated and experimentally determined logKOW values was established (R2 = 0.8024–0.9658).